Poznańska Akademia Przestrzeni jako przykład studenckiego projektu edukacji przestrzennej - Wronkowski , Adam (Studia Edukacyjne, 2021)
Activities aimed at impacting the social space for preschool children are increasingly common. The need to start this type of education from an early age is recognized. In the world and in Poland, many joint actions are being created to familiarize children with the issues related to urban planning, elements of spatial development and the needs of city users. One such program is the Poznań Academy of Space project, implemented since 2016 by the Academic Scientific Association of Spatial Management. The aim of the paper is to present the above project as an example of student activities to increase spatial awareness among the youngest city users. The article presents the theoretical foundations of the project, current activities and plans for the project development in the upcoming years.